Distribution and morphological variation of Synalpheus superus Abele and Kim, 1989 and notes on the distribution of S. fritzmuelleri Coutière, 1909 (Decapoda: Caridea: Alpheidae) - Hermoso-Salazar, Margarita; Solís-Weiss, Vivianne (Zootaxa, 2010)
A significant intraspecific morphological variation was observed in the eastern Pacific snapping shrimp Synalpheus superus Kim & Abele, 1989, especially in the proportions of some cephalotoracic appendages. The northern limit of the distribution of S. superus is expanded from Panama to Guerrero, Mexico. We also consider that Synalpheus fritzmuelleriCoutière, 1909 is most probably not an amphi-American species. Its former status as such was due to taxonomic misinterpretations by Hernández Aguilera et al. (1986) and probably by Coutière (1909) himself, although his questionable record of a single specimen of S. fritzmuelleri from the Gulf of California could not be verified, because the specimen could not be located and may be lost.